A systematic review of the safety of probiotics. (February 2014) - Didari, Tina; Solki, Sara; Mozaffari, Shilan; Nikfar, Shekoufeh; Abdollahi, Mohammad
<x xml:space="preserve">Abstract</x> Introduction: There is growing evidence on the use of probiotics in various diseases, especially in gastrointestinal (GI) diseases. Although probiotics have been found helpful in many illnesses, they do not always seem to be safe. Through interference with commensal microflora, they can result in opportunistic performances in the host due to bacterimia and fungemia. Since considerable numbers of consumers use probiotic products worldwide, assurance of safety of these products is necessary. Areas covered: This review evaluates all the existing information about the safety of probiotics in humans and animal models up to May 2013. In all eligible published studies in which adverse effects and tolerability of probiotics were investigated and reported, no language limitations were applied. The main key search terms were 'probiotics, ' 'safety, ' 'side effects, ' 'clinical trial' and 'adverse effects.' The vast majority of trials investigated Bifidobacterium (B) and Lactobacillus (L) species. Expert opinion: The main observed adverse effects of probiotics were sepsis, fungemia and GI ischemia. Generally, critically ill patients in intensive care units, critically sick infants, postoperative and hospitalized patients and patients with immune-compromised complexity were the most at-risk populations. While the overwhelming existing evidence suggests that probiotics are safe, complete consideration of risk-benefit ratio before prescribing is recommended.